Real-time LEO satellite clock estimation with predicted LEO satellite orbits constrained - Xie, Wei; Su, Hang; Wang, Kan; Liu, Jiawei; El-Mowafy, Ahmed; Yang, Xuhai (Springer Nature, 2024)
Low Earth Orbit (LEO) satellites can augment the traditional GNSS-based positioning, navigation and timing services, which require real-time high-precision LEO satellite clock products. As the complicated systematic efects contained in the LEO satellite clock estimates limit their high-precision mid- to long-term prediction, high-frequency LEO satellite clocks need to be estimated within a Kalman flter, resulting in a short prediction time for real-time applications. Compared to the clock estimation using Batch Least-Squares (BLS) adjustment, flter-based clock estimation experiences a lower precision. Increasing the model strength by introducing external orbital information, thus, de-correlating the orbital and clock param eters, will beneft real-time clock precision. In this contribution, reduced-dynamic LEO satellite orbits are frst estimated using BLS adjustment in near real-time and predicted in the short term. The predicted orbits are then constrained during the Kalman-flter-based clock estimation process. The variance–covariance matrix of the introduced orbital errors is tested for diferent sets of values in the radial, along-track and cross-track directions when constraining orbits of diferent prediction times. One week of GPS data from the Sentinel-3B satellite in 2018 was used for validation of the proposed method. When weakly constraining high-accuracy predicted orbits within a prediction time of 20 min, i.e., with a standard deviation of the constraint set to 2–3 dm in the radial and cross-track directions, and 4–6 dm in the along-track direction, the estimated clock accuracy can be improved from about 0.27 to 0.23 ns, with a 13.4% improvement. Depending on the prediction period of the introduced orbits, the Signal-In-Space Range Error (SISRE) of the LEO satellite to Earth can also be improved, from about 9.59 cm without constraints, to 7.38–8.07 cm after constraining the predicted orbits, with an improvement of 16–23%. The improvements in the SISRE also indicate a better consistency between the real-time clock and orbital estimates.